A human rights-based approach to overfishing in West Africa : comparative study of Guinea-Bissau and the Gambia - Killander, Magnus (University of Pretoria, 2025)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2025.